The Differences of Honest Characters of Students Before and After Learning with A Model of Learning of Intelligent Character - Famahato Lase; Herman Nirwana; Neviyarni Neviyarni; Marjohan Marjohan (RedWhite Press, 2020)
The purpose of this study was to to reveal the differences in honest character of students before and after being taught with a model of learning of inteligent character, using an experimental approach to the one group pretest posttest design method. Subjects, samples, and research data sources are 45 students of Gunungsitoli IKIP. The data collection instrument is a closed questionnaire that is based on seven principles of honest character, namely: speaking as is, acting on the basis of truth, defending the truth, being responsible, fulfilling obligations and accepting rights, being graceful, and keeping promises. The results showed that the intelligent character learning model can improve the honest character of students from not good to very good or from dishonest to very honest. It is recommended that every educator use this intelligent character learning model for all learning activities.